The conflict in Thailand : conditions for a middle way solution - Jeffrey Race (2014)
In the search for a Thai Middle Way solution to the current political crisis, two key conditions have to be fulfilled. In this second of a two-part commentary, the author, a Bangkok-based political consultant, explains the possible way out.